Rare occurrence of small bowel volvulus following laparoscopic appendicectomy for perforated appendicitis. Issue 1 (24th January 2019) - Hegde, Shrenik; Gosal, Preet; Amaratunga, Rajith; Meulman, Neil
Abstract: Intestinal volvulus is a rare complication following laparoscopic surgery. We present the case of a young boy who had developed a small bowel obstruction following laparoscopic appendicectomy for perforated appendicitis. He had no evidence of any congenital malrotation on initial laparoscopy, yet was subsequently found to have a midgut volvulus requiring emergency laparotomy. No resection was required and subsequent convalescence was uncomplicated. This case highlights the importance of recognition of this uncommon but potential early complication of laparoscopy that warrants urgent surgical intervention.